SEDIMENTARY MO ISOTOPE RECORD ACROSS THE HOLOCENE FRESH-BRACKISH WATER TRANSITION OF THE BLACK SEA - Nägler Th.F.; Siebert C.; Lüschen H.; Böttcher M.E. (My University, 2005)
Mo isotope data on Black Sea sediments spanning the transition from Pleistocene oxic–limnic conditions to the prevailing anoxic marine conditions are presented. Samples were taken from a gravity core collected at a water depth of 396 m. Samples deposited under oxic bottom water conditions range from δ98/95MoMOMO − 2.2‰ to − 1.95‰ (MOMO = Mean Ocean Molybdenum) while samples deposited under anoxic bottom water conditions range from δ98/95MoMOMO − 1‰ to − 0.54‰. The change of sedimentary environment is also recorded in the Mo contents increasing from oxic to anoxic sediments. The Mo isotopic composition and invariably low Mo content of the oxic sediments deposited under oxic bottom water conditions are compatible with a pure detrital origin of the Mo, irrespective of whether the deposits are of limnic or brackish origin. Mo content and isotopic compositions are identical above and below a sulfidisation front, which originates from the diffusion of sulfur species and in-situ microbial activity after establishment of brackish bottom water conditions. Further, no signal of the overlaying sapropels is seen in the underlying sediments. Thus, transport of sulfur species has not mobilised Mo during diagenesis.
Keywords: Holocene; Cenozoic::Quaternary::Holocene